If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + 17 = 2z + 13 Reorder the terms: 17 + 3z = 2z + 13 Reorder the terms: 17 + 3z = 13 + 2z Solving 17 + 3z = 13 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. 17 + 3z + -2z = 13 + 2z + -2z Combine like terms: 3z + -2z = 1z 17 + 1z = 13 + 2z + -2z Combine like terms: 2z + -2z = 0 17 + 1z = 13 + 0 17 + 1z = 13 Add '-17' to each side of the equation. 17 + -17 + 1z = 13 + -17 Combine like terms: 17 + -17 = 0 0 + 1z = 13 + -17 1z = 13 + -17 Combine like terms: 13 + -17 = -4 1z = -4 Divide each side by '1'. z = -4 Simplifying z = -4
| 98k^2+84k+18=0 | | Y=5x+1750 | | 4x+7-6x=10+3x+12 | | 14x+5.5+5x+4.5=16x+19 | | -8=5-(9-b) | | 3t^2+43t+14=0 | | 15(a^2)b+22ab+8b=0 | | 4m+8n-6q=0 | | 18=7-(a+10) | | 13x^2-24x-288=0 | | 8m^2+44m+60=0 | | 9(2h+7)+3w= | | k/3=1.5 | | 1/3(8-x)=8-x/2 | | 288=72(h) | | 1/2lnx=-1 | | (2t+7)+6=73 | | 6.28*3/2*13/6x | | 1/2(3j) | | 0.210=3735x-0.006588 | | -(1/3)^1 | | 9t^2-48t+39=0 | | 10n+14=74 | | 3x^2+4x-mn=0 | | .35x=36 | | 5v^2+44v-9=0 | | 3x^2+4x-m*n=0 | | 5v+44v-9=0 | | Ln(x)+ln(x+7)=5 | | Ln(x)-ln(x+7)=5 | | 9h-12h=54-13 | | x+(x)(2)+x-3=39 |